Early Treatment with Empagliflozin and GABA Improves β-Cell Mass and Glucose Tolerance in Streptozotocin-Treated Mice - Caroline Daems; Sophie Welsch; Hasnae Boughaleb; Juliette Vanderroost; Annie Robert; Etienne Sokal; Philippe A. Lysy (Journal of Diabetes Research)
While the autoimmune character of T1D (type 1 diabetes) is being challenged, it is currently recognized that inflammation plays a key role in its development. We hypothesized that glucotoxicity could contribute to β-cell mass destruction through participation in islet inflammation. We evaluated the potential of empagliflozin (EMPA) and GABA (gamma-aminobutyric acid) to protect β-cell mass against glucotoxicity and to increase β-cell mass after diagnosis of T1D. Empagliflozin is a SGLT2 (sodium-dependent glucose cotransporter) inhibitor which thereby blocks glucose recapture by the kidney and promotes glucose excretion in urine. GABA is an inhibitory neurotransmitter, which stimulates α-to-β cell transdifferentiation. In streptozotocin-treated mice, empagliflozin and/or GABA were delivered for a period of five days or three weeks. As compared to untreated T1D mice, EMPA-treated T1D mice had decreased FFA (free fatty acid) levels and improved glucose homeostasis. EMPA-treated T1D mice had higher islet density, with preserved architecture, compared to T1D mice, and EMPA-treated T1D mice also differed from T1D mice by the total absence of immune cell infiltration within islets. Islets from EMPA-treated mice were also less subjected to ER (endoplasmic reticulum) stress and inflammation, as shown by qPCR analysis. Glucose homeostasis parameters and islet area/pancreas area ratio improved, as compared to diabetic controls, when T1D mice were treated for three weeks with GABA and EMPA. T1D EMPA+GABA mice had higher glucagon levels than T1D mice, without modifications of glucagon area/islet area ratios. In conclusion, empagliflozin and GABA, used in monotherapy in streptozotocin-induced diabetic mice, have positive effects on β-cell mass preservation or proliferation through an indirect effect on islet cell inflammation and ER stress. Further research is mandatory to evaluate whether empagliflozin and GABA may be a potential therapeutic target for the protection of β-cell mass after new-onset T1D.